A Route to Commons-Based Democratic Monies? Embedding the Governance of Money in Traditional Communal Institutions - Barinaga, Ester (Frontiers in Blockchain, 2020)
The financial crisis of 2008 resulted, among other, on a popular awareness that the monetary system was not working for the interest of the many. The blockchain technology that was launched soon after offered monetary activists and entrepreneurs a tool to re-imagine, re-claim and re-organise money along a vague ideal of a commons paradigm. A wave of monetary experimentation ensued that took a most concrete form in two entrepreneurial spaces: crypto-currencies with global ambitions and local currencies based on communal democracy. Seemingly distinct on the outset, both strands share a determination to develop a monetary system that serves the many. This has led participants on both sides to reach out towards each other. The article looks at one such attempt: the Sarafu community crypto-currencies in Kenya. These currencies are embedding the creation of money in traditional community savings groups. Using Eleanor Ostrom’s framework and building on interview and ethnographic material, the article identifies the economic logic of mutualization proper of the savings groups as one that transforms private assets (one’s savings) into a financial commons for the group. To build on this logic, the Sarafu model in-the-making is embedding the production and governance of the new community cryptocurrencies in these saving groups. In that doing, Sarafu has the potential to advance a new architecture of money. However, findings suggest that the standardization and automation of the new monetary rules through smart contracts impose neoliberal ideas that slipped into the code, risking the erosion of the very communal decision-making processes that made savings groups interesting anchors of a money commons in the first place.